A quadruplex real-time PCR assay combined with a conventional PCR for the differential detection of Marek’s disease virus vaccines and field strains - Wu, Shaopeng; Ding, Tian; Shao, Hongxia; Qian, Kun; Ye, Jianqiang; Qin, Aijian (Frontiers in Veterinary Science, 2023)
Marek’s disease (MD) is a lymphoproliferative disease in chickens caused by Marek’s disease virus (MDV). The vaccine can prevent tumor development in chickens from virulent MDV infection but could not stop the virus infection. How to evaluate the effect of the vaccine and differentiate vaccine from virulent MDV is difficult in the clinic. In this study, a new quadruplex real-time PCR assay based on TaqMan probes was developed to differentiate and accurately quantify HVT, CVI988 and virulent MDV-1. The results showed that the limit of detection (LOD) of the new assay was 10 copies with correlation coefficients >0.994 of CVI988, HVT and virulent MDV DNA molecules without cross-reactivity with other avian disease viruses. The intra-assay and inter-assay coefficients of variation (CVs) of Ct values for the new assay were less than 3%. Analysis of replication kinetics of CVI988 and virulent MDV of collected feathers between 7 and 60 days post-infection (dpi) showed MD5 had no significant effect on the genomic load of CVI988 (p > 0.05), while vaccination with CVI988 could significantly reduce the viral load of MD5 (p < 0.05). Combined with meq gene PCR, this method can effectively identify virulent MDV infections in immunized chickens. These results demonstrated that this assay could distinguish between the vaccine and virulent MDV strains and had the advantages of being reliable, sensitive and specific to confirm the immunization status and monitor the circulation of virulent MDV strains.